2021
DOI: 10.14693/jdi.v28i1.1150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P ect of Passive Tobacco Smoking Exposur obacco Smoking Exposure on the P e on the Periodontal eriodontal Status of Turkish Children

Abstract: Objective: This study aimed to assess the effect of passive tobacco smoking (PTS) through the comparison of the periodontal status and the C-reactive protein (CRP) and cotinine levels in the biologic fluids in children who are exposed and unexposed to PTS. Methods: A total of 148 participants, whom had smokers (PTS-exposed, n=82) and non-smokers (PTS-unexposed, n=66) in their families, respectively, were included in the study. Gingival index, plaque index, probing depth, and bleeding on probing were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…This result is in agreement with the one reported in Iran by Mosharrafian et al [ 17 ], who suggested that passive smoking led to an increase in dental plaque accumulation. Nevertheless, this finding is in contrast to the one reported in Turkey [ 24 ]. This could be explained by the same mechanism of active smoking, which causes bacterial dental plaque build-up.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in agreement with the one reported in Iran by Mosharrafian et al [ 17 ], who suggested that passive smoking led to an increase in dental plaque accumulation. Nevertheless, this finding is in contrast to the one reported in Turkey [ 24 ]. This could be explained by the same mechanism of active smoking, which causes bacterial dental plaque build-up.…”
Section: Discussioncontrasting
confidence: 99%